KONSILI VATIKAN II, 50 TAHUN KEMUDIAN - Andreas A. Yewangoe (Institut Filsafat dan Teknologi Kreatif Ledalero, 2013)
The Second Vatican Council has its own resonance which has impacted not only the Roman Catholic Church but other Churches also, indeed the world as a whole. This was the conviction of Pope John XXIII when he announced his idea for a Universal Council. He wished to place the Church within the rapidly changing modern world. One change is in attitudes towards other religions which has opened the path towards dialogue. Now, 50 years later, can the council still speak to us about Church renewal and unity? We note progress in Indonesia such as dialogue between religions and religious convictions, the ecumenical movement which has spread, for instance through the acceptance of a common translation of the Bible. In NTT Province theology faculty members of the Christian University (UKAW) in Kupang and the Philosophy Institute of Ledalero (STFK), Maumere exchange faculty and students. Kata-kata Kunci: Pembaruan, gerakan ekumene, kesatuan, misi Gereja, solidaritas